Principal Component Analysis and Causal Modeling in the Valorization of Banana Pseudostems for Biodegradable Materials - Cardenas, Erika Jadira Romero; Santillán, Xiomara Leticia Zúñiga; Romero, Byron Ramiro Romero; Núñez, Diego Wladimir Tapia; Rodríguez, Edwuin Jesús Carrasquero (Migration Letters, 2024)
The study focused on evaluating the opinions of banana producers in Ecuador regarding the use of natural fibers from banana plant pseudostem as a sustainable alternative to produce biodegradable materials. Expert-validated surveys were conducted with 197 managers and owners of banana farms in Zone 5. The research employed a quantitative methodology for data collection. A descriptive analysis of the survey instrument items assessed the distribution and dispersion of the data, along with a correlation analysis between instrument categories. A multivariate PCA was used to condense the data and identify the principal components that explain variations in responses. A causal model based on these principal components was then created and tested for statistical fit. The findings revealed that participants generally viewed the identified elements-initiatives and sustainability mechanisms-favorably. The research indicates that banana pseudostems could be a viable option to produce biodegradable products, addressing the growing waste problem in the banana industry.